Dirāsah Tahlīliyah Manhaj Ta’lim Allughah Al’arabiyah Fī Almadrasah Altsaanawiyah Bayt Al arqam Kolaka - Hilyatun Aulia; Fahmi Ridha (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2022)
This study aims to determine the Arabic learning curriculum at Madrasah Aliyah Baitul Arqom Polinggona and to determine the advantages and disadvantages of the curriculum. This research uses qualitative, analytical, and field research methods. In collecting data, the researcher used the method of observation, interviews, and document review. The conclusion of this research was that the Arabic language learning curriculum at Madrasah Aliyah Baitul Arqom Polinggona applied the 2013 national curriculum and the local curriculum as well. The advantages of the curriculum included, requiring students to be more independent, creative and innovative, the assessment process was carried out from all aspects, and encouraging teachers to be more creative in the teaching process. As for the shortcomings, namely the many and complicated assessment systems, lack of adequate facilities and infrastructure in carrying out the curriculum and too many subjects that must be mastered by students. Penelitian ini bertujuan untuk mengetahui kurikulum pembelajaran bahasa Arab di Madrasah Aliyah Baitul Arqom Polinggona Kolaka. Penelitian ini menggunakan pendekatan kualitatif dan metode deskriptif. Dalam mengumpulkan data, peneliti menggunakan metode observasi, wawancara, dan telaah dokumen. Kesimpulan dari hasil penelitian ini bahwa pembelajaran bahasa Arab di Madrasah Aliyah Baitul Arqom Polinggona menerapkan kurikulum 2013 dan kurikulum kepesantrenan. Diantara kelebihannya yaitu, menuntut siswa lebih mandiri, kreatif dan inovatif, proses penilaian dilakukan dari semua aspek, dan mendorong guru untuk semakin kreatif. Adapun kekurangannya, yaitu sistem penilaian yang rumit, kurangnya sarana dan prasarana yang memadai dan materi yang wajib dikuasai terlalu banyak.